Pengaruh Social Media Marketing, Content Marketing, dan (e¬-WOM) Terhadap Keputusan Pembelian di Oha Doku - Nafisa Eka Puspita; Irwansyah Irwansyah; Firmansyah Firmansyah (Journal of Management and Creative Business, 2026)
This quantitative research aims to dissect the impact of e-WOM, content marketing, and social media marketing on purchasing decisions in OHA Doku culinary business in Dompu Regency. Sampling was conducted purposively to 96 respondents considering the characteristics of an infinite population, supported by PLs-SEM analysis techniques using SmartPLS 3.0. From the analysis conducted, it was found that purchasing decisions were only significantly influenced by content marketing, while social media marketing and e-WOM showed no influence. Facebook Instagram, WhatsApp, and Oha Doku are recommended to focus more on developing an interesting and informative content marketing strategy on WhatsApp, Instagram, and Facebook, including displaying testimonials and the behind-the-scenes process of making products. This strategy should also be balanced with E-WOM optimization, where business owners motivate consumers to write good reviews that are then amplified to local Facebook communities and WhatsApp Stories to boost public trust and expand the reach of promotions.